Remove the Wounds in the City (Policy) for Lepers in Surabaya in the 19th Century - Moordiati Moordiati (Universitas Airlangga, 2020)
This article aims to discuss about the treatment of people with leprosy (leprosy) in Surabaya during the nineteenth century. The maltreatment can not be ignored since their existence was never really desirable in the city, let alone the many stigmas that had already been attached to them. It is not unusual if people had the desire to